A model of functional integration and conflict: The case of purchasing-production in a construction company. Issue 3 (25th February 2014) - Ellegaard, Chris; Koch, Christian
Abstract : Purpose: – The purpose of this article is to generate theory on how functional integration and conflict interrelate by studying the interface between production and purchasing. Design/methodology/approach: – An interpretive single case research methodology is adopted. The authors rely on in-depth interviewing of managers in the production and purchasing functions of a construction company, as well as by its suppliers. Findings: – Given low functional integration, antagonistic reasoning within each function and resultant conflicting behaviors are allowed to develop in a negative cycle, escalating the conflict between purchasing and production. This process leads to the creation of two opposing functional sourcing models that serve as blueprints for behavior. Research limitations/implications: – The single case methodology was chosen to maximize depth and detail and form an ideal foundation for theory building. Future qualitative and quantitative studies should inquire further into the studied phenomenon to increase analytical and statistical generalizability of the proposed model. Practical implications: – The findings can help managers understand how poor integration between functions can develop into cross-functional conflict. Facing a conflicting functional relationship, managers must resort to conflict resolution methods, instead of attempting to integrate, as several integrative devices are not appropriate in conflicting interfaces. Originality/value: – The proposed model contributes by connecting the constructs of integration, group reasoning, and conflict, thereby generating knowledge on conflict development processes in cross-functional interfaces. Furthermore, the article contributes by uncovering the difficulties associated with implementing spend consolidation, a prevailing sourcing strategy.